The future of work, technology, and basic income - Cholbi, Michael; Weber, Michael (Routledge research in applied ethics, 2020)
Technological advances in computerization and robotics threaten to eliminate countless jobs from the labor market in the near future. These advances have reignited the debate about universal basic income. The essays in this collection offer unique and compelling perspectives on the ever-changing nature of work and the plausibility of a universal basic income to address the elimination of jobs from the workforce. The essays address a number of topics related to these issues, including the prospects of libertarian and anarchist justifications for a universal basic income, the positive impact of a basic income on intimate laborers such as sex workers and surrogates, the nature of "bad work" and who will do it if everyone receives a basic income, whether a universal basic income is objectionably paternalistic, and viable alternatives to a universal basic income. This book raises complex questions and avenues for future research about universal basic income and the future of work in our increasingly technological society. It will be of keen interest to graduate students and scholars in political philosophy, economics, political science, and public policy who are interested in these debates